Estrutura da avifauna e sua relação com serviços ecossistêmicos da bacia do rio Monjolinho, São Carlos, SP - Lessi, Bruno Flório (Universidade Federal de São Carlos, 2019)
As birds are a well-known class of animals, occurring in almost all habitats, where they perform essential ecosystem functions, they are indicated as good bioindicators of ecosystem services (ES). Many services provided by birds arise through their ecological functions and their benefits are often transmitted indirectly, thus they are hardly understood or measured in terms of their contribution to human well-being. In this sense, this project aims to evaluate the relationship of the bird community with ES, not only the services promoted directly as birds, but also the ES of the environment itself that is related to its biodiversity. We selected 43 survey points distributed along riparian ecosystems, covering the entire Monjolinho River basin (São Carlos / SP), aiming to (1) analyze community structure in relation to the seasonality, land use and occupation influences, functional diversityand supply of ES; (2) to evaluate the seed disperser community with an improvement in the understanding of this ES provided by birds and its seasonal and spatial distribution in the study area; and (3) to investigate a relationship between bird richness and current state of ES as Cooling effect, air pollution retention and Nature-based recreation opportunities and their dynamic along an urbanization gradient. The results point to a well-structured community with 201 species and few seasonal variations, and remain with high richness at all points, even in urbanized areas. The functional diversity observed is linked to 8 ES types according to species’ ecological functions. The land use mapping showed a vast mosaic composed predominantly byanthropic areas such as agriculture and urbanization. The in-depth analysis of the seed dispersion ES, promoted by at least 39 species during two seasons, indicated significant changes in species composition and in taxonomic diversity and distinction between the rainy and dry seasons of the year, and higher quality of the dispersion service supply in environments with a higher proportion of native vegetation. The study over the relationship between bird richness and ES showed a significantly positive relationship between bird richness, air pollution retention and microclimate regulation, and negative with the recreation opportunities. These results can be used as a basis for better urban planning and for the definition of priority areas for environmental enrichment in order to expand the ES supplyas a guarantee of biodiversity conservation and increase in the human well-being.
Avifauna structure and its relationship with ecosystem services in the Monjolinho River basin, São Carlos, SP
Keywords: Aves; Guildas; Funções ecológicas; Sazonalidade; Mapeamento; Uso e ocupação da terra; Birds; Guilds; Ecological functions; Seasonality; Mapping; Land use and land cover; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS